Antecedents of Customer Loyalty in the South African Life Insurance Industry - Mkhize, Basil (University of the Witwatersrand, Johannesburg, 2024)
ii ABSTRACT Retaining existing customers is currently the most significant challenge in the competitive life insurance market (Lakshmi & Santhi, 2015). Yet, previous studies on the factors influencing customer loyalty and repeat purchases have primarily been conducted in industries other than life insurance. Customer loyalty has been widely explored in marketing; however, empirical research on this subject within the life insurance sector in South Africa is scarce (Minta, 2018). Furthermore, there is a notable increase in lapse rate as the source of customer dissatisfaction in the life insurance sector (Sivesan (2019). Thus, the study explored the antecedents of customer loyalty in South Africa’s life insurance industry. It examined the impact of service quality, complaint handling, customer satisfaction, and trust on customer loyalty to South African life insurance. Additionally, it investigated the mediating factors affecting customer loyalty in the South African life insurance industry using the expectancy-confirmation theory. The methodology involved a self-administered questionnaire from 303 life insurance policy owners in South Africa. Structural equation modelling was used to test eight hypotheses, including two mediating effects. IBM SPSS 27, AMOS 27, and SmartPLS 3 software were used to analyse and interpret the dataset. The study found that six of the eight tested hypotheses were supported and significant, with service quality having the greatest impact on customer satisfaction. Furthermore, customer satisfaction was found to mediate the relationship between service quality and customer loyalty partially, and customer trust partially mediated the relationship between complaint handling and customer loyalty. This suggests that marketing managers in South African Life Insurance could use these results to enhance their service delivery strategies to maximise customer satisfaction and ultimately increase their retention goals. This study contributes to the literature on customer loyalty to life insurance companies by investigating its antecedents, including the mediating roles of customer satisfaction and trust, which have been under- researched. Furthermore, several future research directions which marketers and scholars could undertake are highlighted.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Strategic Marketing to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Service quality; Complaint handling; Customer satisfaction; Customer trust and customer loyalty; UCTD; SDG-8: Decent work and economic growth